Norwidowskie interpretacje chrześcijańskiego Seneki - Karamucka-Marcinkiewicz, Magdalena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Connections with Christianity are one of the aspects of reflections on the life and work of Seneca the Younger in subsequent centuries. This issue is also revealed in the writings of Cyprian Norwid, a Polish 19th-century writer, artist and thinker. In point of fact, Norwid skipped other aspects related to Seneca. The themes he did touch on are connected with his historiosophical reflections and the problem of the relationship between Roma pagana and Roma Christiana, which was of particular interest to him. In the preserved writings of Norwid, however, references to Seneca are relatively rare, which was actually quite typical in the 19th century, but may also be related to a certain ambiguity in Seneca’s attitude as the tutor of Emperor Nero and a figure who enjoyed a high position in Rome for a long time or Norwid’s conviction that most of Seneca’s thought close to Christianity should simply be explained by the Roman writer’s stoicism. However, this is only a hypothesis. It is also possible that Norwid more often referred to Seneca the Younger than he literally noted it. Norwid referred, among other things, to the issue of alleged relations between Seneca and St. Paul and the apocryphal correspondence between them. He also referred to Seneca’s importance for the Church Fathers. Furthermore, he drew attention to some similarities between Seneca and Socrates in terms of their martyr deaths and to certain thoughts expressed by Seneca, in which one can perceive the idea of one God. Some of Norwid’s references to Seneca analysed here were inspired by such works devoted to Seneca’s Christianity as the article by Gaston Boissier, which was published in 1871 in the “Revue des Deux Mondes”. It is not exactly clear how well Norwid knew the work of Seneca, and to what extent he relied on the aforementioned studies. Undoubtedly, however, the references to Seneca, which he included in his writings, were carefully selected and were related to Norwid’s vision of history and his deliberations on the essence of truth, and thus they were not only a testimony of Norwid’s reading, but also of Norwid’s personal reflections.